Some Advances in the Study of Error Expansion for Finite Elements (Journal of Computational Mathematics, 2021)
For the eigenvalue problem on a smooth domain we prove that the Richardson extrapolation increases the accuracy from second to third order for linear finite elements, and from fourth ro fifth order for quadratic finite elements, without modification of the scheme near the boundary.